Investigating Problems that Matter for Young People: Reauthoring Possibilities for Social-Emotional Learning in English Language Education - Siobhan O’Brien; Mark Vicars; Jordan González (Anglica. An International Journal of English Studies)
This article reports on a qualitative case study with families of young English as an additional language (EAL) children in year 3–4 classrooms in metropolitan Melbourne, Australia. In the context of this inquiry, developmental bibliotherapy, which uses books to “heal the mind,” was operationalized as a social-emotional learning (SEL) tool, using a transactional reader response approach. In this SEL approach, children made life-to-text and text-to-life connections that focused on three topic areas: body image, resilience, and self-esteem through the reading encounter. Findings shed light on the pedagogical implications of developmental bibliotherapy as an SEL tool and an eudaimonic factor in young EAL children’s life worlds.